Characterization of the Functions of Starch Synthase IIIb Expressed in the Vegetative Organs of Rice (Oryza sativa L.). (12th October 2022) - Morita, Ryutaro; Crofts, Naoko; Miura, Satoko; Ikeda, Ken-ichi; Aoki, Naohiro; Fukayama, Hiroshi; Fujita, Naoko
Abstract: Rice is the model C3 crop for investigating the starch biosynthesis mechanism in endosperm because of its importance in grain production. However, little is known about starch biosynthesis in the vegetative organs of rice. In this study, we used novel rice mutants by inserting Tos17 into the starch synthase (SS) IIIb gene, which is mainly expressed in the leaf sheath (LS) and leaf blade (LB), and an ss1 mutant to clarify the differences in roles among SS isozymes during starch biosynthesis. Native polyacrylamide gel electrophoresis (PAGE)/activity staining for SS, using LS and LB of ss mutants, revealed that the lowest migrating SS activity bands on the gel were derived from SSIIIb activity and those of two ss3b mutants were not detected. The apparent amylose content of LS starch of ss3b mutants increased. Moreover, the chain-length distribution and size-exclusion chromatography analysis using ss mutants showed that SSIIIb and SSI synthesize the B2 –B3 chain and A–B1 chain of amylopectin in the LS and LB respectively. Interestingly, we also found that starch contents were decreased in the LS and LB of ss3b mutants, although SSI deficiency did not affect the starch levels. All these results indicated that SSIIIb synthesizes the long chain of amylopectin in the LS and LB similar to SSIIIa in the endosperm, while SSI synthesizes the short chain in the vegetative organ as the same in the endosperm.